Mass spectrometric analysis of peptides from an immobilized lipase: focus on oxidative modifications. - Törnvall, Ulrika; Melin Fürst, Camilla; Hatti-Kaul, Rajni; Hedström, Martin (Rapid Communications in Mass Spectrometry, 2009)
Liquid chromatography/tandem mass spectrometry (LC/MS/MS) was used to study the primary structure of immobilized Candida antarctica lipase B (Novozym(R)435) without detaching the enzyme from the carrier. The immobilized enzyme packed in a miniature column was subjected to proteolysis and the peptides released were injected into the mass spectrometer for analysis. The set-up was utilized to determine amino acid oxidation after treatment of the biocatalyst with hydrogen peroxide. In total, sequence coverage of more than 90% was obtained, containing almost all of the amino acids sensitive to oxidation. Oxidation of methionine, tryptophan and cystine residues was observed. The flow system also allowed evaluation of the enzyme activity prior to peptide analysis. The developed method is general and should be applicable to other immobilized enzyme systems and to different treatments.